Massive illegal immigration of sub-Saharan Africans as a language of counter-hegemony - ITSHENU GETUMBE, Dieudonné; Blaise Iyamba Valentin, (IJRDO - Journal of Social Science and Humanities Research, 2019)
In the search of the explanation of struggle between the weak and the strong in increasingly globalized world lies the question of migration. This article examines the fundamental motivations behind the migration of sub-Saharan Africans with the main objective of analyzing the situation of the current migration crisis between the countries of the South and those of the North before determining the deepen causes of clandestine immigration of Sub-Saharan Africans. As much as it generates so much debates both in newspapers columns and in television channels, African migration appears to be a social phenomenon with multiple and varied stakes and is now one of the major contemporary international political problems including : terrorisme, the proliferation of nuclear weapons and climate change. The migration of Africans, victims rightly or wrongly, of Western hegemony  now participates in the deconstruction of the existing traditional geopolitics.